2007
DOI: 10.4049/jimmunol.179.3.1842
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis Serotype 2, an Important Swine and Human Pathogen, Induces Strong Systemic and Cerebral Inflammatory Responses in a Mouse Model of Infection

Abstract: Streptococcus suis, an important swine and human pathogen, causes septic shock and meningitis. The pathogenesis of both systemic and CNS infections caused by S. suis is poorly understood. A hematogenous model of infection in CD1 mice was developed to study the systemic release of cytokines during the septic shock phase and the proinflammatory events in the CNS associated with this pathogen. Using a liquid array system, high levels of systemic TNF-α, IL-6, IL-12, IFN-γ, CCL2, CXCL1, and CCL5 were observed 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
234
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(261 citation statements)
references
References 68 publications
27
234
0
Order By: Relevance
“…In agreement with the findings of previous studies (20,21,26), patterns of bacterial burdens observed in spleen and liver were similar to those observed in blood samples, with no significant differences being detected among strains (data not shown). These results suggest that the increased virulence of S. suis ST7 cannot be explained by an increase in blood bacterial burden and that other factors account for its pathogenic potential.…”
Section: Difference In Virulence Among North American European Andsupporting
confidence: 82%
See 1 more Smart Citation
“…In agreement with the findings of previous studies (20,21,26), patterns of bacterial burdens observed in spleen and liver were similar to those observed in blood samples, with no significant differences being detected among strains (data not shown). These results suggest that the increased virulence of S. suis ST7 cannot be explained by an increase in blood bacterial burden and that other factors account for its pathogenic potential.…”
Section: Difference In Virulence Among North American European Andsupporting
confidence: 82%
“…Our laboratory previously developed a mouse model of S. suis systemic infection (20,21). Infected animals can succumb rapidly, and this mortality can be associated with septic shock symptoms.…”
mentioning
confidence: 99%
“…These observations are intriguing given the purported role of IFN-␥ in the pathogenesis of several diseases, such as multiple sclerosis, sepsis, human immunodeficiency virus-associated dementia, and Alzheimer's (14,19,32,79,81). The results of the present study can lend insight into results from current clinical trials involving the administration of IFN-␥ as adjuvant therapy (49) and possibly the design of future trials involving IFN-␥ blockade.…”
Section: Discussionmentioning
confidence: 76%
“…Lecours et al (2011) showed that CPS impairs cytokine release by hindering cell wall components; thus, reduced levels of CPS could result in exposing bacterial cell wall components and facilitate an increased inflammatory response. Studies on meningitis-associated bacteria have shown that a fatal disease outcome can be caused by the host inflammatory response (Dominguez-Punaro et al 2007). Dominguez-Punaro et al (2010) showed that after being stimulated by an SS CPS-deficient mutant, the microglia induced significantly higher levels of proinflammatory mediators than that of the wild-type strain.…”
Section: Discussionmentioning
confidence: 99%